Social capital and community development: Where do we go from here?. Issue 1 (1st January 2022) - Halstead, John M.; Deller, Steven C.; Leyden, Kevin M.
ABSTRACT: Social capital has become a cornerstone to community development. Unfortunately, its scope of research, particularly on policy, creates more smoke than light. This essay builds on an interdisciplinary foundation for a more inclusive approach to social capital research. Though broad evidence supports Putnam's claims on social capital, our understanding is incomplete, partly due to scholars' focus on individual disciplinary perspectives. We summarize social capital and its use as a development tool, and consider how to move toward a more interdisciplinary framework. We explore where communities have created and evaluated social capital, cross-disciplinary insights, empirical work suggesting cause-effect, and offer three examples of interplay between social capital and community development: the built environment, migration, and entrepreneurship. Our conclusion presents a conceptual model including all Community Capitals rather than treating them piecemeal, viewing the community as a system under what ecologists call the "law of the minimum" wherein limiting elements constrain growth.